Assessment of Hypertension and the Associated Risk Factors in Postmenopausal Rural Women in Bangladesh: A Study from Basic Epidemiology to Biomarker Assessment. (June 2015) - Jesmin, Subrina; Rahman, Md Arifur; Akter, Shamima; Islam, Majedul; Khatun, Tanzila; Sultana, Sayeeda Nusrat; Zaedi, Sohel; Okazaki, Osamu; Iwashima, Yoshio; Kawano, Satoru
Abstract : Poster Presentation: Hypertension (HTN) appears as a modern epidemic, a silent killer causing an estimated 7.1 million premature deaths and 4.5% of disease burden (64 million disability adjusted life years DALYs) thus a grave concern for the humanity. Although Bangladeshi populations are considered as having greater risk for HTN, however, there is no representative published data for prevalence or incidence of HTN in Bangladesh. The proposed study is mainly designed to estimate the prevalence of hypertension (HTN), and its potential risk factors to Bangladeshi population especially the postmenopausal rural women as they getting less attention at all levels. This study is based on across-sectional study among 1382 post-menopausal women. We used the World Health organization's STEPS approach (modified), which entails a stepwise collection of the risk factor data, based on standardized questionaries, covering demographic characteristic, somatic illness, somatic and mental illness, somatic and mental symptoms, medications, lifestyle, and health related behavior (step 1), basic physical measures (step 2), and basic bio-chemical investigations, such as blood glucose and cholesterol (step 3). Out of 1382 post-menopausal women 680 (49.2%) was found to have hypertension and 548 (39.65%) post-menopausal women have metabolic syndrome. We divide the post-menopausal women into hypertensive and non-hypertensive group. Hypertensive post-menopausal women were relatively older (55 years) than non-hypertensive group (52 years). Post-menopausal hypertensive women have higher body much index (BMI), and waist circumference (WC) than non-hypertensive post-menopausal women. (BMI, HTN vs. non-HTN: 22.5 vs. 21.2; WC, HTN vs. non-HTN: 77.8 vs. 75.9, P  < 0.05). Post-menopausal hypertensive women have significant higher level of high-density lipoprotein cholesterol, systolic blood pressure, diastolic blood pressure, fasting blood glucose, and fasting insulin level than non-hypertensive women (P < 0.05). As prevalence of coronary heart disease (CHD) is an alarming epidemic in women at menopause, then we investigated the potent crucial angiogenic growth factor for coronary microcirculation namely vascular endothelial growth factor (VEGF) and its two important receptors (VEGFR1 and VEGFR2) in this study setting. Circulatory level of VEGF was not significantly altered among post-menopausal hypertensive than non-hypertensive women, but there is a trend of increasing level of VEGF in hypertensive (HTN vs. non-HTN: 522.01 vs. 465.51). sVEGF-R1 (soluble form of VEGFR1) level was significantly lower in post-menopausal hypertensive women than non hypertensive (HTN vs. non-HTN: 437.78 vs. 631.25, P  = 0.04). There was no significant difference in sVEGFR-2 (soluble form of VEGFR2) level among post-menopausal hypertensive than non-hypertensive women. Thus it seems there is a potential disruption in the delicate balance of VEGF and the soluble forms of VEGF receptors in the postmenopausal women with hypertension.